Verification of selective and individual pulmonary thromboembolism prophylaxes for cesarean delivery - Ryuji Kawaguchi; Tomoka Maehana; Yuki Yamada; Mayuko Ichikawa; Juria Akasaka; Fuminori Kimura (Korean Society of Obstetrics and Gynecology, 2023)
Objective This study aimed to verify the utility of simple, safe, and effective venous thromboembolism (VTE) prophylaxis and implement it with few adverse events during cesarean delivery. Methods This single-center, prospective study involved pregnant women who underwent cesarean deliveries from August 3, 2020 to March 31, 2022. Patients with VTE risk factors were initially administered unfractionated heparin (5,000 international unit [IU] subcutaneously, twice daily), 6 hours after cesarean delivery. Subsequently, they were administered enoxaparin (2,000 IU subcutaneously, twice daily). They were not administered anticoagulants if one or more of the exclusion criteria were met. The primary efficacy outcome was the incidence of symptomatic VTE. The primary safety outcome was the incidence of major bleeding. Results Out of the 850 women eligible for this study, 551 (64.9%) had one or more VTE risk factors and 299 (35.1%) had no risk factors. Of the 551 women with one or more VTE risk factors, 15 met one or more exclusion criteria for enoxaparin administration. A total of 314 women received only perioperative mechanical prophylaxis, including 15 who met the exclusion criteria for anticoagulants and 299 without VTE risk factors. During implementation of the protocol, no woman developed symptomatic VTE after cesarean delivery. Major bleeding occurred in only one woman who received postoperative anticoagulants. Conclusion This protocol, which clarified the administration of anticoagulants according to VTE risk factors and dose reduction/discontinuation criteria, may be an effective and safe VTE prophylaxis for cesarean deliveries.